Osmotic response in Leptospirillum ferriphilum isolated from an industrial copper bioleaching environment to sulfate - Arias, Dayana; Zepeda, Víctor; Nancucheo, Ivan; Saldaña, Manuel; Galleguillos, Pedro A. (Frontiers in Microbiology, 2024)
Iron and sulfur-oxidizing microorganisms play important roles in several natural and industrial processes. Leptospirillum (L.) ferriphilum, is an iron-oxidizing microorganism with a remarkable adaptability to thrive in extreme acidic environments, including heap bioleaching processes, acid mine drainage (AMD) and natural acidic water. A strain of L. ferriphilum (IESL25) was isolated from an industrial bioleaching process in northern Chile. This strain was challenged to grow at increasing concentrations of sulfate in order to assess changes in protein expression profiles, cells shape and to determine potential compatible solute molecules. The results unveiled changes in three proteins: succinyl CoA (SCoA) synthetase, isocitrate dehydrogenase (IDH) and aspartate semialdehyde dehydrogenase (ASD); which were notably overexpressed when the strain grew at elevated concentrations of sulfate. ASD plays a pivotal role in the synthesis of the compatible solute ectoine, which was identified along with hydroxyectoine by using matrix-assisted laser desorption/ionization-time of flight mass spectrometry (MALDI-TOF). The relationship between IDH, SCoA, and ectoine production could be due to the TCA cycle, in which both enzymes produce metabolites that can be utilized as precursors or intermediates in the biosynthesis of ectoine. In addition, distinct filamentous cellular morphology in L. ferriphilum IESL25 was observed when growing under sulfate stress conditions. This study highlights a new insight into the possible cellular responses of L. ferriphilum under the presence of high sulfate levels, commonly found in bioleaching of sulfide minerals or AMD environments.